DEPOSITI DELTIZI PLIOCENICI ALLO SBOCCO DELLA VAL BREMBANA (PREALPI BERGAMASCHE) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
At the outlet of the Brembo valley into the upper Lombardy Plain a conglomerate unit is present, about 30 m thick and outcropping over an area of about 1.5 km 2 . This conglomerate was in the past attributed to the Villafranchian and considered as the lowermost part of the "Ceppo", a thick and widespread formation composed of well cemented coarse fluvial deposits.The conglomerate unit here described, called Madonna del Castello Conglomerate, is interpreted as a Late Pliocene deltaic deposit. It shows a large scale cross—stratification affecting the whole thickness of the unit; single beds show decreasing gradient from the top to the base, with a concave up profile. Beds are prevailingly composed of matrix supported conglomerate, with elongated clasts parallel to the dip of bedding. Both geometry and structures are indicative of foreset beds.The petrographic composition of the Madonna del Castello Conglomerate is characterized by prevailing clasts of Mesozoic limestones of local provenance, while subordinate and often absent are metamorphic, volcanic and arenaceous rocks deriving from the Sudalpine crystalline basement and from its Paleozoic cover, which outcrop at the head of the Brembo valley.The Madonna del Castello Conglomerate overlies Early to Middle Pliocene fossiliferous mudstones (Tornago Formation) and represents a terminal regressive phase of the marine Pliocene sedimentation at the foot of the Lombardy Prealps.